2021
DOI: 10.1136/bmjqs-2021-013493
|View full text |Cite
|
Sign up to set email alerts
|

Should electronic differential diagnosis support be used early or late in the diagnostic process? A multicentre experimental study of Isabel

Abstract: BackgroundDiagnostic errors unfortunately remain common. Electronic differential diagnostic support (EDS) systems may help, but it is unclear when and how they ought to be integrated into the diagnostic process.ObjectiveTo explore how much EDS improves diagnostic accuracy, and whether EDS should be used early or late in the diagnostic process.Setting6 Canadian medical schools. A volunteer sample of 67 medical students, 62 residents in internal medicine or emergency medicine, and 61 practising internists or eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 36 publications
3
40
0
Order By: Relevance
“…To date, several studies have been conducted to evaluate the impact of the timing of using a diagnostic decision support system. According to their studies, physician diagnosis was associated with their first impression [ 50 ], and early use of diagnostic support systems before collecting information by physicians significantly improved the diagnostic accuracy [ 21 - 23 ]. These findings may support the positive effects of the implementation of an automated medical history–taking system with a differential diagnosis generator, which can provide diagnostic decision support before physicians collect information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several studies have been conducted to evaluate the impact of the timing of using a diagnostic decision support system. According to their studies, physician diagnosis was associated with their first impression [ 50 ], and early use of diagnostic support systems before collecting information by physicians significantly improved the diagnostic accuracy [ 21 - 23 ]. These findings may support the positive effects of the implementation of an automated medical history–taking system with a differential diagnosis generator, which can provide diagnostic decision support before physicians collect information.…”
Section: Discussionmentioning
confidence: 99%
“…Computerized automated history-taking systems perform better in clinical documentation tasks for taking patient histories than do physicians [ 19 , 20 ]. The use of a diagnostic support system (ie, differential diagnosis generator) before collecting information by physicians showed a significant impact on the improvement of diagnostic accuracy in terms of clinical reasoning and differential diagnosis [ 21 - 23 ]. Moreover, a new system that combines automated medical history–taking functions with differential diagnosis generation—specialized for musculoskeletal diseases only—showed improved diagnostic accuracy among physicians in a pilot randomized controlled trial [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, many researchers and clinicians have become skeptical of the tool due to initial over-promises from the company ( 164 ). Many other diagnostic support applications have been developed, most of them aimed at commercial use such is the case of ISABEL https://www.isabelhealthcare.com/ ( 165 , 166 ) and others. However, due to commercial restrictions, their AI/ML assessment and their use in LSDA has been rather restricted ( 167 , 168 ).…”
Section: Challenges To Computational Learning In Precision Medicinementioning
confidence: 99%
“…improve diagnostic accuracy. 12 However, prior research on the effectiveness of CDS at preventing other types of adverse events has shown that CDS typically have a small impact on the quality and safety of care. This is because CDS are often implemented without accounting for the social and technical context in which they will be used.…”
Section: Box 1 Example Of Diagnostic Error Casementioning
confidence: 99%
“…Many hospitals—including ours—already have technology-based system interventions (such as electronic health record (EHR) alerts based on physiological variables) to help clinicians identify patients with sepsis, with the goal of initiating evidence-based treatment in a timely fashion. There is some evidence in simulation studies that the use of clinician decision support systems (CDS) that generate a list of possible diagnoses can help improve diagnostic accuracy 12. However, prior research on the effectiveness of CDS at preventing other types of adverse events has shown that CDS typically have a small impact on the quality and safety of care.…”
Section: Present Limitations In the Diagnostic Error Literaturementioning
confidence: 99%